2020
DOI: 10.1111/flan.12454
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of app‐based language instruction for developing receptive linguistic knowledge and oral communicative ability

Abstract: Hundreds of millions of language learners around the globe study a second language with popular apps such as Duolingo, Rosetta Stone, Busuu, and Babbel. This study examined the effectiveness of one app, Babbel, for developing both receptive linguistic knowledge of vocabulary and grammar, as well as oral communicative ability in Spanish as a second language. Fifty‐four English speakers not enrolled in Spanish classes studied Spanish on Babbel over the course of 12 weeks, with a goal of studying roughly 10 min p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
37
1
3

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(43 citation statements)
references
References 39 publications
2
37
1
3
Order By: Relevance
“…To support struggling readers, some of the effective features of iPad applications include vocabulary support (e.g., Loewen, Isbell, & Sporn, 2020; Ludwig, 2018; Retter, Anderson, & Kieran, 2013) as well as self‐regulation (e.g., Vogelgesang, Bruhn, Coghill‐Behrends, Kern, & Troughton, 2016; Wills & Mason, 2014; Xin, Sheppard, & Brown, 2017). For example, Loewen et al (2020) examined the effectiveness of the iPad application for second language learning to develop students' knowledge of vocabulary, grammar and oral communication in Spanish. The iPad application allowed students to learn progressive lessons within the application by using subsequent lessons that successively build upon key instructional components covered in the previous lessons.…”
Section: Tablet‐based Intervention For Students With Reading Difficulmentioning
confidence: 99%
“…To support struggling readers, some of the effective features of iPad applications include vocabulary support (e.g., Loewen, Isbell, & Sporn, 2020; Ludwig, 2018; Retter, Anderson, & Kieran, 2013) as well as self‐regulation (e.g., Vogelgesang, Bruhn, Coghill‐Behrends, Kern, & Troughton, 2016; Wills & Mason, 2014; Xin, Sheppard, & Brown, 2017). For example, Loewen et al (2020) examined the effectiveness of the iPad application for second language learning to develop students' knowledge of vocabulary, grammar and oral communication in Spanish. The iPad application allowed students to learn progressive lessons within the application by using subsequent lessons that successively build upon key instructional components covered in the previous lessons.…”
Section: Tablet‐based Intervention For Students With Reading Difficulmentioning
confidence: 99%
“…Babbel afirma que permite hablar una lengua meta desde el primer día, lo cual no encaja necesariamente con la experiencia de aprendizaje de este tutorial, lastrada por la falta de interacción y producción abierta o semiabierta. Sin embargo, un estudio reciente, patrocinado por Babbel, demuestra de forma empírica que la aplicación permite a sus usuarios desarrollar el conocimiento de vocabulario y gramática y, más importante, su capacidad de comunicación oral al nivel principiante en español (Loewen, Isbell y Sporn, 2020). En 12 semanas, más de la mitad de los 54 participantes fueron capaces de incrementar un subnivel dentro del nivel principiante, con un test que mide su capacidad de comunicación oral.…”
Section: Posicionamiento Didácticounclassified
“…In the past 20 years, considerable research regarding online instruction in higher education demonstrated that students who were enrolled in full online learning programs were faced with a system shock and were not familiar with such experience (Fawaz, Samaha, 2020). In recent years, online learning has emerged as one of the most effective educational approaches and the role of technology in foreign language development is a crucial topic (Loewen, Isbell, & Sporn, 2020;Reinders & Stockwell, 2017; Rosell-Aguilar, 2018). Thus, today's online learning offers valuable educational materials employing a variety of media, as well as the capacity to enable both synchronous and asynchronous communication between teachers and students (Aboagye, 2020; Means, Toyama, Murphy, Bakia, & Jones, 2009).…”
Section: Introductionmentioning
confidence: 99%